Aesthetic Leadership in Chinese Business: A Philosophical Perspective - Zhang, Haina; Cone, Malcolm H.; Everett, André M.; Elkin, Graham (2011)
Confucian ethics play a pivotal role in guiding Chinese thinking and behaviour. Aesthetic leadership is emerging as a promising paradigm in leadership studies. This study investigates the practice of aesthetic leadership in Chinese organizations on the basis of Chinese philosophical foundations. We adopt a process perspective to access the aesthetic constellation of meanings present in the Chinese understanding of leadership, linking normative Confucian values to a pragmatic value rational world view, that rests on an ontology of vaguely defined norms that are malleable to different cultural contexts. Value rational pragmatism is explored in order to develop a deeper understanding of normative aesthetic leadership in China and to contrast it to instrumental aesthetic leadership. We empirically demonstrate the contextual specificity of aesthetic leadership in eight Chinese private- and state-owned enterprises (POEs and SOEs) through qualitative case studies. The findings provide a deeper insight into Chinese aesthetic leadership by proposing a dynamic leadership approach, from both ethical and instrumental perspectives, in the Chinese context.
Keywords: China; Instrumentalism; Pragmatism; Confucian Ethics; aesthetic leadership